Identification and Analysis of Potential Breast Anticancer Agents in Pogostemon Cablin through Network Pharmacology - Syarifah Fathimah Azzahra; Essy Harnelly; Muhammad Subianto; Wisnu Ananta Kusuma; Widya Sari (Jurnal Penelitian Pendidikan IPA, 2024)
Breast cancer is one of the highest known causes of death in Indonesia, especially for women. Pogostemon cablin Benth is one of the Aceh's endemic herbal plants that has been studied to have potential such as anti-inflammatory, antiproliferative, antioxidant, antimicrobial, and proapoptotic. Network pharmacology approach was conducted to explore and analyze the potential of P. cablin as an anti-breast cancer. P. cablin plant compounds were obtained from GCMS and breast cancer genes data were obtained from OMIM, GeneCard, and DisGeNet databases. Target proteins and pathways involved were identified using STRING-DB and Metascape. Network analysis was performed using Cytoscape. A total of 65 plant compounds with 554 target proteins and 1854 disease genes were obtained. Based on the results of combining protein targets using Venn diagrams, 138 overlapping proteins between drug compounds and breast cancer disease targets were identified. Based on KEGG and GO analysis, P. cablin is known to have potential in breast cancer treatment/therapeutic mechanisms. Based on the "compound-protein target-pathway" multi-target mechanism, pogostol; 1H-Cycloprop[e]azulen-7-ol, decahydro-1,1,7-trimethyl-4-methylene-, [1ar-(1aα,4aα,7β,7aβ,7bα)]-; 3-Hexen-1-ol, 2,5-dimethyl-, acetate, (Z)-, 5β,7βH,10α-Eudesm-11-en-1α-ol; Acetic acid, 3-hydroxy-6-isopropenyl-4,8a-dimethyl 1,2,3,5,6,7,8,8a-octahydronaphthalen-2-yl ester; and Humulenol-II interacts with proteins that play a significant role in breast cancer, which are MAPK1, EGFR, TNF, AKT1, and JAK2. Hence, it can be concluded that P. cablin has good potential to be a source of therapeutic treatment against breast cancer. However, it needs to be tested clinically to further determine the effects of this P. cablin compound.